Circular Economy Based City Park Management Model in Surabaya Indonesia - Dwi Haryanta; Tatuk Tojibatus Sa’adah; Achmadi Susilo; Indarwati (Agricultural Science, 2025)
Maintaining a green, clean, beautiful, and lush city park through the year requires sustainable management, which includes maintenance like watering, pruning, trimming, and rejuvenation, as well as the creation of new parks. This study aims to identify the factors that influence the successful management of city parks in Surabaya and to understand the organic material cycle involved in managing these parks. This study used qualitative descriptive method. Data were collected through interviews with park management personnel, documentation from various city government policies, and field observations related to park management activities. Data were analysed using triangulation methods. Trees and city parks need regular care, such as pruning and trimming, to provide optimal benefits. Pruning waste, along with other organic waste, is composted at composting facilities or recycling centers widely available in Surabaya. The cyclical management of organic waste from city parks impacts the growth and development of Surabaya's parks while simultaneously solve the problem of organic waste produced by city communities.Although many studies discuss urban green space and waste management in Surabaya, specific research mapping the biomass cycle and circular economy framework in city park management is still limited. Therefore, this study aims to fill that research gap by exploring how circular economy principles are implemented in the Surabaya city park management system.